Jackson and Schuler (1985) Revisited: A Meta-Analysis of the Relationships Between Role Ambiguity, Role Conflict, and Job Performance - Tubre, Travis C.; Collins, Judith M. (Journal of Management, 2000)
We conducted a meta-analysis of correlations between role ambiguity and job performance and role conflict and job performance. Previous meta-analyses of these role constructs and performance relationships (e.g., Jackson & Schuler, 1985) were limited by small sample sizes and sparse reporting of reliability estimates in primary studies. The present study used a comprehensive database with a larger sample size and a distribution of interrater reliabilities to extend the previous findings. We also tested moderator hypotheses proposed but not conducted by Jackson and Schuler. Results revealed a negative relationship (r52.21) between role ambiguity and job performance with moderating influences due to job type and rating source. A negligible relationship (r52.07) was observed for role conflict and job performance, a finding consistent across job types and rating sources. Conclusions were that role ambiguity ought not to be dismissed as an unimportant variable in the job performance domain.